Assessment of knowledge and preventive behavior regarding rubella virus among females in Riyadh, Saudi Arabia: A cross-sectional study - Jehad A. Aldali (PLoS ONE, 2025)
Background Rubella is an acute viral infection that is influenced by various factors, e.g., climate, dietary habits, and hygiene practices. This study evaluated the knowledge and preventive behaviors regarding Rubella infection among females in Riyadh, Saudi Arabia. Methods In this cross-sectional study, an online Arabic and English survey was administered using Google Forms. The survey was distributed to female participants from March 25, 2024 to May 27, 2024. The first section of the online survey covered age, gender, education level, and marital status information. The second section assessed the participants’ knowledge of rubella, including its transmission methods, symptoms, severity, concerns, and effects on pregnant females and their embryos. Finally, immunization status and prevention mechanisms were addressed in the third section. Results The online survey was completed by a total of 448 female participants. The participants consisted of 53.8% young participants (ages 18–25) from a variety of educational backgrounds, with 62.3% of them being single. The Rubella virus was acknowledged by the majority of participants (57.6%). Specifically, 57.6% of the participants asserted that they were aware of the rubella infection. Nevertheless, 51.6% were unaware of the methods by which rubella is transmitted. Furthermore, 55.4% of the participants reported that they were unaware of the significant health risks associated with rubella. The fact that 59.8% of the participants were unaware of rubella complications raises several significant questions. Fever and skin rash were identified as the most frequently reported symptoms, accounting for 23.4% of all cases. We examined the reasons for non-vaccination among the unvaccinated participants and discovered that 36.2% cited a lack of awareness. More than half of the participants (64.1%) consistently adhere to hygienic practices. Conclusion The findings of the study indicates that females in Riyadh possess adequate knowledge concerning the rubella virus. When information is available, there exists a readiness to acquire knowledge and implement preventive measures. Increased education regarding the rubella virus may enhance individuals’ willingness to engage and adopt proactive measures. Therefore, enhancing rubella prevention behaviors is crucial to mitigate the risk of infection, notwithstanding the advantages of general hygiene practices.